Variability in the Use of Audiovisual Translation Terminology - Kerevičienė, Jurgita; Astrauskienė, Jurgita (Respectus Philologicus, 2021)
The growing supply of audiovisual products is closely linked to their translation to the target audience. In Lithuania, as well as in other countries, various modes of audiovisual translation are applied: some audiovisual works are dubbed, some are translated using voice-over, and still others are subtitled or surtitled. Deaf and hard of hearing viewers have access to the audiovisual content with the help of specialized subtitles; whereas the blind and partially sighted gain access via audio description. Each mode of audiovisual translation is defined by particular terms and specific characteristics, the variety of which may frequently seem like a kind of terminological maze for their users. This article aims at defining terms related to both the field of audiovisual translation and its modes by examining their differences and similarities to provide a structured classification of these terms. The paper also presents the insights and results of the survey, which reveals consumers’ ambiguities about the perception of audiovisual products and the application of audiovisual translation terminology.